Hyperactive-impulsive behavior does not moderate the association between executive function and physical activity in preschoolers - Anne Eppinger Ruiz de Zarate; Julia Kerner auch Körner; Petra Haas; Catherine Gunzenhauser; Wolfgang Rauch; Caterina Gawrilow (Scientific Reports)
Abstract Experimental research suggests a positive association between executive function (EF) and physical activity (PA). Observational research examining PA in everyday life does not consistently support this positive association, with findings yielding negative or no associations. Hyperactive-impulsive behavior could act as a possible moderator, explaining inconsistent findings. In this observational study, we examined the relation between EF and everyday PA as well as hyperactive-impulsive behavior as a potential moderator in a sample of 68 German preschoolers (3–5 yrs). As performance-based measured of EF and PA, participants performed a computerized EF test battery in two sessions and wore an accelerometer for 7 days. Parental questionnaires of EF, PA, and hyperactive-impulsive behavior were further implemented. Accelerometer-assessed moderate-to-vigorous PA was negatively related to EF performance, and hyperactive-impulsive behavior did not moderate this association. Neither time spent in any other PA intensity nor parental PA reports were related to EF. The present study represents the first study to investigate if hyperactive-impulsive behavior moderates the association between everyday PA and preschoolers’ EF. Thus, the findings yield new insight into the relation between PA in everyday life and preschoolers’ EF, as the unexpected negative relation could not be explained through hyperactive-impulsive behavior.